Aspectos da ciclagem de nutrientes em um sistema silvopastoril com Acacia mearnsii De Wild., no município de Tupanciretã, RS - Calil, Francine Neves (2003)
This study had as objective to quantify the biomass above and below ground of the Acacia mearnsii De Wild. trees and of the Panicum maximum Jacq., as well as determine these contents in the biomass and soil and evaluate the ecological and silviculture implications of the silvopasture system. It was carried in a 6 years old Acacia mearnsii settlement, located in an experimental area belonging to FEPAGRO, in Tupanciretã, RS, having as geographic coordinates 29° 03’ 10” of south latitude and 53° 50’ 44” of west longitude. After the forest inventory, 21 trees were selected and cut, being quantificated the biomass and nutrients in the leaves, live and dead branches, bark, wood and roots of the black wattle, and biomass above and below ground of the fodder. 40 samples of litter were collected for nutrients and biomass quantification, and 4 trenches were opened for physical and chemical soil characterization. The coefficients of the equation log = b0 + b1 * ln d, were determined to the estimate the biomass components. The total biomass production was of 140,73 Mg ha-¹, allocated 4,3 in the leaves; 15,8 % in the dead branches, 5,3 % in the live branches, 7,3 % in the bark, 54,6 % in the wood and 12,5% in the roots. This biomass contained the total amount of 622,19; 59,36; 186,94; 404,00; 88,27; 48,37; 1,36; 0,22; 6,15; 2,02; 1,65 kg ha-¹ of the elements N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn respectively. The backloged litter biomass over de soil was 9,1 Mg ha-¹, having as average of 141,96, 7,28, 25,48, 70,98, 7,28, 12,74, 0,24, 0,03, 31,79, 1,75, 0,77 kg ha-¹ of the elements N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn respectively. The Panicum biomass production was of 2,21 Mg ha-¹, being 1,63 Mg ha-¹ above the ground and 0,58 Mg ha-¹ below ground, containing 34,58, 3,39, 21,56, 12,08, 6,97, 3,75, 0,023, 0,012, 0,585, 0,516, 0,040 kg ha-¹ of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn above ground, e 9,96, 0,97, 3,72, 1,78, 0,68, 0,88, 0,018, 0,004, 0,434, 0,105 3 0,010 kg ha-¹ of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn below ground.